(untitled) - Burger, Edward ([Austin, Tex.], 2004)
The content includes real numbers; equations and inequalities; exponents and polynomials; rational expressions; roots and radicals; relations and functions; the straight line; systems of equations; quadratic equations and inequalities; conic sections; inverse, exponential, and logarithmic functions
Keywords: Algebra,Algebra